2018
DOI: 10.24136/eq.2018.019
|View full text |Cite
|
Sign up to set email alerts
|

Relative effectiveness of monetary and fiscal policies on output growth in Turkey: an ARDL bounds test approach

Abstract: Research background: Effects of monetary and fiscal policy on output growth has been one of the major topics that economists have been investigating. Monetary and fiscal policies are tools for economists and policymakers to correctly direct the economy and facilitate the growth and development of the country. Accordingly, it is critically important for policy-makers in the area of economy to study the efficiency and the effectiveness of such policies. But, so far, there has been no generally accepted evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…As pointed out in (Özer & Karagöl, 2018), The relationship between fiscal and monetary policies and growth has conducted a lot of number of empirical investigation come up with mixed conclusion across different cross sectional, time series and panel data, such as, OLS, Panel data models, VAR model, VEC Model and ARDL Model. The majority of the finding confirmed that fiscal and monetary policies are certainly affect growth.…”
Section: Emperical Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…As pointed out in (Özer & Karagöl, 2018), The relationship between fiscal and monetary policies and growth has conducted a lot of number of empirical investigation come up with mixed conclusion across different cross sectional, time series and panel data, such as, OLS, Panel data models, VAR model, VEC Model and ARDL Model. The majority of the finding confirmed that fiscal and monetary policies are certainly affect growth.…”
Section: Emperical Literature Reviewmentioning
confidence: 99%
“…Similarly, the study conducted by Özer and Karagöl (2018) who analyzed the relative growth effectiveness of fiscal and monetary policies in Turkey over the period 1998 and 2016 by using the techniques of ARDL Bounds testing, structural Granger causality tests and their result indicates that Monetary policy variable is creating only short-run effects on growth; but, does not cause any Granger causality on it, that is fiscal policy variable has a long-run significant effect and causing to growth. As result they concluded that the fiscal policy seems to be more effective than monetary policy during examination period, implying the rethinking the implementation of both policies to achieve past economic growth.…”
Section: Emperical Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations